2019
DOI: 10.3168/jds.2018-14879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arginase inhibition via jugular infusion of Nω-hydroxy-nor-l-arginine on metabolic and immune indices in lactating dairy cows

Abstract: Transformation of Arg to nitric oxide and ornithine (Arg-Orn) constitutes the main route of Arg metabolism in mammals. The primary objective of this work was to determine the effects of inhibiting the Arg-Orn pathway via N ω-hydroxy-nor-l-arginine (nor-NOHA) on health of lactating cows. Furthermore, we also explored the effect of Arg-Orn inhibition on the efficiency of nitrogen utilization to find support for previous research that showed the inhibition of Arg-Orn inhibited milk protein synthesis. Six healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Colostrum composition, including lactose, fat, protein, total solids, and nonfat solids, was determined using a MilkoScan FT 120 (Foss Electric, Hillerød, Denmark). Commercial ELISA kits [MBS702497 (detection range: 1.56-100 μg/mL), MBS282896 (detection range: 0.16-10.00 μg/mL), and MBS285353 (detection range: 31.25-2,000 μg/mL), respectively; MyBioSource Inc., San Diego, CA] were used to determine IgA, IgM, and IgG concentrations of colostrum and calf serum IgA, IgM, and IgG, respectively, as described by Ding et al (2019). The interassay coefficients of variation were lower than 10%, and the intraassay coefficients of variation were lower than 12%.…”
Section: Sample Analysesmentioning
confidence: 99%
“…Colostrum composition, including lactose, fat, protein, total solids, and nonfat solids, was determined using a MilkoScan FT 120 (Foss Electric, Hillerød, Denmark). Commercial ELISA kits [MBS702497 (detection range: 1.56-100 μg/mL), MBS282896 (detection range: 0.16-10.00 μg/mL), and MBS285353 (detection range: 31.25-2,000 μg/mL), respectively; MyBioSource Inc., San Diego, CA] were used to determine IgA, IgM, and IgG concentrations of colostrum and calf serum IgA, IgM, and IgG, respectively, as described by Ding et al (2019). The interassay coefficients of variation were lower than 10%, and the intraassay coefficients of variation were lower than 12%.…”
Section: Sample Analysesmentioning
confidence: 99%
“…The organism of animal is a complex biological selfreplicating self-regulatory system that has adapted during evolution to exist in relatively unstable environmental conditions. In the course of long phylogeny in mammals, clear mechanisms of interaction between microorganisms and the organism of animals and humans were formed, and the immune protection system was evolved, and immunity was formed (Ceniti et al, 2017;Ding et al, 2019). In the modern sense of immunity means the ability of the body to protect itself from genetically extraneous (as well as other pathogenic factors), aimed at maintaining biological homeostasis (Kurjogi & Kaliwal, 2014;Günther et al, 2017;.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, nutritional strategies are effective ways to improve the functions of PMN. Arginine is another essential and functional AA for dairy cows (NRC, 2001) and plays an important role in immune function (Wu and Meininger, 2002;Ding et al, 2019). Savoini et al (1984) found that defensins in bovine PMN are rich in cysteine and Arg (38-42 residues) and display bactericidal activity against many gram-positive, gram-negative, and anaerobic bacteria as well as fungi and viruses.…”
Section: Introductionmentioning
confidence: 99%